Recent Challenges and Methodologies in Smart Grid Demand Side Management: State-of-the-Art Literature Review. (9th August 2021) - Nasir, Tehreem; Bukhari, Syed Sabir Hussain; Raza, Safdar; Munir, Hafiz Mudassir; Abrar, Muhammad; Muqeet, Hafiz Abd ul; Bhatti, Kamran Liaquat; Ro, Jong-Suk; Masroor, Rooha
Abstract : The concept of smart grid was introduced a decade ago. Demand side management (DSM) is one of the crucial aspects of smart grid that provides users with the opportunity to optimize their load usage pattern to fill the gap between energy supply and demand and reduce the peak to average ratio (PAR), thus resulting in energy and economic efficiency ultimately. The application of DSM programs is lucrative for both utility and consumers. Utilities can implement DSM programs to improve the system power quality, power reliability, system efficiency, and energy efficiency, while consumers can experience energy savings, reduction in peak demand, and improvement of system load profile, and they can also maximize usage of renewable energy resources (RERs). In this paper, some of the strategies of DSM including peak shaving and load scheduling are highlighted. Furthermore, the implementation of numerous optimization techniques on DSM is reviewed.